2016
DOI: 10.1007/s13277-016-4919-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-130b promotes proliferation and EMT-induced metastasis via PTEN/p-AKT/HIF-1α signaling

Abstract: Hepatocellular carcinoma (HCC) is a major cause of cancer-related deaths owing to its high rate of postoperative recurrence and metastasis. New research is continuously identifying novel metastasis-associated oncogenes and tumor suppressor genes. miRNAs are noncoding RNAs that regulate protein synthesis post-translationally. miR-130b is one of several miRNAs involved in tumor metastasis. However, the role of miR-130b in HCC remains controversial. Here, we demonstrate that miR-130b is highly expressed in HCC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 36 publications
2
38
2
Order By: Relevance
“…The results suggested an association between miR-320 and HIF-1α in adjusting RB progression. Increasing evidence has shown that miRNA interfere with the metastasis and invasion of various types of cancer via the regulation of HIF-1α (21)(22)(23)(24). In this study, a luciferase reporter assay was employed to investigate the effect of miR-320 on HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested an association between miR-320 and HIF-1α in adjusting RB progression. Increasing evidence has shown that miRNA interfere with the metastasis and invasion of various types of cancer via the regulation of HIF-1α (21)(22)(23)(24). In this study, a luciferase reporter assay was employed to investigate the effect of miR-320 on HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that EWS-FLI1 is capable of modulating miRNA expression; however, miR-130b expression was not shown to be altered in these studies 48,49 . While miR-130b has been independently shown to contribute to metastatic properties in other malignancies, we cannot exclude the contribution of the fusion transcript to aid in metastatic potential dictated by miR-130b 7,50 . Overall, we highlight this as a potential mechanism to promote metastasis in Ewing sarcoma, but cannot exclude other mechanisms of action such as input from other GTPases or components of the MAPK pathway.…”
Section: Discussionmentioning
confidence: 92%
“…48,49 While miR-130b has been independently shown to contribute to metastatic properties in other malignancies, we cannot exclude the contribution of the fusion transcript to aid in metastatic potential dictated by miR-130b. 7,50 Overall, we highlight this as a potential mechanism to promote metastasis in ES, but cannot exclude other mechanisms of action such as input from other GTPases or components of the MAPK pathway. Future and ongoing studies include testing of relevant inhibitors of the MAPK and JNK as well as PAK1 in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations